2007
DOI: 10.1016/j.apgeochem.2007.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in groundwater from mineralised Proterozoic basement rocks of Burkina Faso

Abstract: This study describes the hydrogeochemistry and distributions of As in groundwater from a newly investigated area of Burkina Faso. Groundwaters have been sampled from handpumped boreholes and dug wells close to the town of Ouahigouya in northern Burkina Faso.Although most analysed groundwaters have As concentrations of less than 10 µg L -1 , they have a large range from <0.5 to 1630 µg L -1 . The highest concentrations are found in borehole waters; all dug wells analysed in this study have As concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
66
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 29 publications
8
66
1
Order By: Relevance
“…In contrast to surface waters, the origin of the high levels of arsenic in groundwater is mainly natural. So, the high concentrations of arsenic reported in the groundwater by Smedley et al (2007) in Burkina Faso (1630 μg L −1 ) and Kusimi and Kusimi (2012) in Ghana (1760 μg L −1 ) have for origin weathered rocks of the underlying geology and are not due to mining activities. When considering the concentrations of arsenic in surface waters (0.5 to 73 μg L −1 ) and in groundwaters (<0.1 to 4 μg L −1 ) from Tarkwa (Asante et al 2007), or the ones in Obuasi ranging from <2 to 175 μg L −1 and from <2 to 64 μg L −1 , respectively, in surface waters and groundwater (Smedley 1996), two gold mining areas in Ghana, it can be noticed that mining activities affect less the groundwaters than surface waters.…”
Section: Arsenic In Groundwatermentioning
confidence: 91%
“…In contrast to surface waters, the origin of the high levels of arsenic in groundwater is mainly natural. So, the high concentrations of arsenic reported in the groundwater by Smedley et al (2007) in Burkina Faso (1630 μg L −1 ) and Kusimi and Kusimi (2012) in Ghana (1760 μg L −1 ) have for origin weathered rocks of the underlying geology and are not due to mining activities. When considering the concentrations of arsenic in surface waters (0.5 to 73 μg L −1 ) and in groundwaters (<0.1 to 4 μg L −1 ) from Tarkwa (Asante et al 2007), or the ones in Obuasi ranging from <2 to 175 μg L −1 and from <2 to 64 μg L −1 , respectively, in surface waters and groundwater (Smedley 1996), two gold mining areas in Ghana, it can be noticed that mining activities affect less the groundwaters than surface waters.…”
Section: Arsenic In Groundwatermentioning
confidence: 91%
“…In the past years, more and more countries have found their waters to be affected by arsenic contamination due to mining wastes, e.g., Poland, Korea and Brazil (Marszałek and Wasik, 2000;Woo and Choi, 2001;Borba et al, 2003). More recently, groundwater in Burkino Faso was measured to be contaminated by arsenic, up to 1630 µg L −1 , caused by mining activities (Smedley et al, 2007). Furthermore, Gunduz et al (2009) reported elevated arsenic levels (max.…”
Section: Arsenic In Groundwater: a Worldwide Problemmentioning
confidence: 99%
“…Only contamination by pathogenic microorganisms has a bigger impact worldwide. Figure 1 Arsenic-affected countries (red) of the world (Smedley and Kinniburgh, 2002;Appleyard et al, 2006;Petrusevski et al, 2007;Smedley et al, 2007;Gunduz et al, 2009) Arsenic contamination of groundwater has been found to occur due to geothermallyinfluenced groundwater, mineral dissolution (e.g., pyrite oxidation), desorption in the oxidising environment, and reductive desorption and dissolution (Smedley and Kinniburgh, 2002). Table 1 gives an overview of the arsenic concentrations Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There remain many instances of 'drilling blind' in rural water-supply provision, constructing unnecessarily deep waterwells, and failing potable drinking-water quality standards (due to hazardous or troublesome constituents such as fluoride, soluble iron or salinity; Chilton and Foster 1995;Edmunds and Smedley 2005;Smedley et al 2007). Such problems are widely increasing the unit cost of rural water-supply provision, and in some areas mean that adequate sources are not being provided.…”
Section: Improving the Efficiency Of Rural Village Water-supply Provimentioning
confidence: 99%